Culture and customs of Ghana - Salm, Steven J., 1966- (Culture and customs of Africa., 2002)
Endorsement From Emmanuel K. Akyeampong Department of History Harvard University: This book is a vivid portrayal of Ghanaian culture and customs. It is a masterful synthesis of massive information into a very accessible and highly readable text that will appeal to both academic and non-academic audiences. The accurate and highly pertinent review of history, religion, literaure and media, art and architecture, cuisine and dress, music and dance, marriage and family, social customs and lifestyle makes this book an important treasure even for Ghanaianists, who seldom find all this useful information within the covers of a single volume. The authors certainly have their fingers on the pulse of cultural and social life! Endorsement From Kwabena O. Akurang-Parry Department of History Shippensburg University: This is the best book on Ghana that takes stock of various aspects of the Ghanaian society and culture. One of the greatest strengths of this book is its detailed information based on examples from various sectors of the Ghanaian society.; The book, very informative, readable, and erudite, takes cognizance of "tradition," transformations, and modernizing realms of Ghanaian norms and institutions ... Highly recommended for students of African studies and the general public. The decades of independence in Ghana have strengthened the idea of a national Ghanaian culture. The culture and customs of Ghana today are a product of diversity in traditional forms, influenced by a long history of Islamic and European contact. Culture and Customs of Ghana is the first book to concisely provide an up-to-date narrative on the most significant elements of the established cultural life and institutions as well as the most recent changes in the cultural landscape. Written expressly for students and the general reader, it belongs in every library supporting multicultural and African studies curricula. Ghana seeks to cultivate the philosophy of the "African personality," to revive, maintain, and promote Ghanaian ways of life and integrate them into political and social institutions. Ghanaians also recognize their relationship to the rest of the world and continue to develop with the forces of globalization.; Culture and Customs of Ghana authoritatively discusses the vibrant and adaptable people, from their religions to music and dance. A chronology, glossary, and numerous photos complement the text